Nanocarreador baseado em quitosana tiolada e nanopartícula de ouro como sistema de liberação controlada para o fármaco antineoplásico docetaxel - Teixeira, Genisson Barbosa (2018)
Drug delivery systems based on gold nanomaterials are regarded as one of the most effective methods for the treatment of cancer. In this work, we developed a nanocarrier based on a thiol-organofunctionalized chitosan and gold nanoparticles (AuNPs)for docetaxel, an antineoplastic drug used for the treatment of lung, prostate, leukemia and malignant melanoma tumors. Initially, chitosan (CS) was modified with cysteine (CYS) by coupling them using N,N′-Dicyclohexylcarbodiimide (DCC). The presence of thiols groups in CS was confirmed by FTIR spectroscopy. Subsequently, AuNPs were synthesized and passivated by sodium citrate. From UV-vis spectroscopy analysis, it was possible to obtain a strong absorbance band at 520 nm, which is related to the localized surface plasmon resonance (LSPR). The size distribution of the nanoparticles was obtained by TEM, showing an average size of around 18nm. Then, a study using UV-vis spectroscopy, DLS, zeta potential and SEM was performed to understand the formation of the nanocomposite AuNPs/CS-SH. In this study, it was observed that the nanoparticles systematically aggregate in the presence of the polymeric matrix, changing their optical and morphological properties through time and amount of CS-SH. The release profile of the DTX with CS-SH was twice as much as the free drug, as well as, the material gave a controlled release up to 48 hours and constant up to 120 hours, unlike the free drug. After that time, the absorbance values remained constant until approximately 80 hours, unlike the free drug. The use of the zero order kinetic model allowed a better understanding of the drug release profile with the material.